2023
DOI: 10.3390/jcm12196135
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal-Based Microsurgical Breast Reconstruction: How to Inset the Flap to Maximize the Aesthetic Result—A Systematic Review

Gianluca Sapino,
Sherilyn K. Tay,
Michele Maruccia
et al.

Abstract: Nowadays, the ultimate goal of microsurgical breast reconstruction is not merely the effective transfer of vascularized tissue but the achievement of a natural, symmetric appearance. The aim of this present study was to systematically summarize the published evidence on abdominal-based free flap inset for breast reconstruction in order to provide principles and classification that could guide the surgeon in choosing the most appropriate inset technique based on patient and flap characteristics. A comprehensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
0
0
Order By: Relevance
“…Several techniques have been described, considering the type of donor site, volume and skin to be replaced, laterality and anatomical characteristics of the source vessels and their perforators, as well as the recipient vessels. However, there is only a small body of scientific evidence regarding the aesthetic outcome of flap-based breast reconstruction that emphasizes flap inset and shaping techniques [14]. Even less represented are studies evaluating patient-reported outcome measures (PROMs) with regard to the aesthetic satisfaction in abdominal flap-based breast reconstruction depending on the shaping and inset techniques.…”
Section: Of 15mentioning
confidence: 99%
“…Several techniques have been described, considering the type of donor site, volume and skin to be replaced, laterality and anatomical characteristics of the source vessels and their perforators, as well as the recipient vessels. However, there is only a small body of scientific evidence regarding the aesthetic outcome of flap-based breast reconstruction that emphasizes flap inset and shaping techniques [14]. Even less represented are studies evaluating patient-reported outcome measures (PROMs) with regard to the aesthetic satisfaction in abdominal flap-based breast reconstruction depending on the shaping and inset techniques.…”
Section: Of 15mentioning
confidence: 99%